Bullous pemphigoid associated with anti‐programmed cell death protein 1 and anti‐programmed cell death ligand 1 therapy: A case series of 13 patients. (13th December 2022) - Yun, Jenny S. W.; Chan, On Bon; Goh, Michelle; McCormack, Christopher J.
Abstract: We present a case series of 13 patients, the first Australian single‐centre study of bullous pemphigoid (BP) associated with immune checkpoint inhibitors (ICI): cytotoxic T‐lymphocyte antigen (CTLA4) and programmed cell death receptor (PD1) inhibitors. All our patients achieved adequate control of BP with a combination of treatments including oral prednisolone, intravenous immunoglobulin, rituximab and omalizumab. The majority of patients ceased or interrupted immunotherapy treatment upon diagnosis of BP and greater tumour progression was seen in the cohort who ceased immunotherapy.